Analysis of the Effect of Cash Holding and Liquidity on Company Value: The Role of Company Size as a Moderating Variable - Nur Aini Rojabiyah; Syaiful Syaiful (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The purpose of this study is to investigate how cash holdings and liquidity affect firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2023 and 2024, using firm size as a moderating variable. This study adopts a quantitative approach utilizing secondary data sourced from corporate annual reports. The sample was determined through purposive sampling, yielding 176 observations. The data were examined using multiple linear regression and Moderated Regression Analysis (MRA), with all variables converted into natural logarithmic form to satisfy classical assumption criteria. The findings indicate that cash holdings exert a positive and significant influence on firm value, and liquidity likewise has a significant impact on firm value. The moderation analysis further reveals that firm size amplifies the effect of cash holdings on firm value. In contrast, firm size does not moderate the relationship between liquidity and firm value. These findings suggest that effective cash management is essential for improving firm value, especially in larger firms, while the contribution of liquidity to firm value is not contingent upon firm size. This study implies that corporate management should place greater emphasis on efficient cash management strategies to enhance firm value and investor confidence.